PENGARUH PBL BERBANTUAN MEDIA UANG MAINAN TERHADAP CAPAIAN BELAJAR SISWA KELAS I - Ratna Ayu Kusumaningtyas; Noor Miyono; Agus Riyadi; Bagus Ardi Saputro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Efforts to shape and educate the next generation of the nation to grow into individuals who are faithful and noble, knowledgeable, virtuous, skilled and independent are carried out through education. In the 21st century teachers not only play an important role in improving learning outcomes, but equipping students with four skills namely critical thinking, creativity, collaboration, and communication. The research was motivated by the low learning outcomes of students due to the use of limited learning methods and media, as well as the classical learning process. This study aims to determine the effect of PBL implementation with the help of toy money on learning outcomes of grade IB students at SDN Bendungan in Indonesian language subjects. This study used a quantitative approach with Pre-Experimental Design. The results showed a significant increase in student learning outcomes after applying the PBL model with the help of concrete media. The average score of students' pretest increased from 20-90 to 40-100 in the posttest. This increase was mainly due to students' active participation in the learning process and the use of concrete media that made learning more interesting and meaningful. The hypothesis shows the value of tcount > ttable which is 8.917 > 2.06866 and the value of Sig. (2-tailed) < a which is 0.000 < 0.05. From the results of the study, it can be concluded that the PBL learning model assisted by toy money is effective in improving the learning outcomes of IB grade students of SDN Bendungan.